Palms of Southern Asia - Henderson, Andrew, 1950- (Book collections on Project MUSE., 2009)
Southern Asia is a vast and ecologically diverse region that extends from the deserts of Afghanistan to the rainforests of Thailand, and is home to a marvelously rich palm flora. Palms of Southern Asia is the only complete field guide to the 43 genera and 352 species of palms and rattans that occur in Afghanistan, Bangladesh, Bhutan, Cambodia, China, India, Japan, Laos, Myanmar, Nepal, Pakistan, Sri Lanka, Taiwan, Thailand, and Vietnam. This attractive guide's handsome illustrations and succinct, authoritative, and jargon-free text make identification easy. Each species account inclu.